Diffusion NMR: A Tool to Investigate the Dynamics of Organic Systems - Stait-Gardner, Timothy; Torres, Allan; Zubkov, Mikhail; Willis, Scott A.; Zheng, Gang; Price, William S. (Current Organic Chemistry, 2018)
Background: Self-diffusion, the random molecular motion of molecules in the absence of a chemical potential, is readily measured with pulsed field gradient NMR techniques. Measurements of diffusion can provide information on chemical binding and porous microstructure. Objective: This manuscript describes the basics of self-diffusion measurement by NMR and provides a justification for the Stejskal-Tanner expression for free diffusive attenuation. After a discussion of the Pulsed Gradient Spin Echo (PGSE) and Pulsed Gradient STimulated Echo (PGSTE) sequences, some more specialised methods are discussed. These include: (i) A description of the effects of J-coupling during a diffusion measurement and J-compensated PGSE. J-interactions create combinations of in-phase and antiphase peaks and can make analysis difficult. (ii) Rapid NMR methods for diffusion measurement. This includes a technique enabling shorter recycle delays and circumventing the need to wait 51 for the magnetisation to recover before running the next iteration of the sequence. (iii) An introduction to obstruction and diffusion averaging effects. This is quite an involved topic but some of the fundamentals are presented here. (iv) Solvent signal suppression in high-field NMR. Solvent signals can cause problems for diffusion measurements too. The requirements for a good solvent suppression sequence are discussed followed by an introduction to the WaterControl technique. Conclusion: The variety of techniques that are presented, and which are built around PGSE/PGSTE, show the versatility of Diffusion NMR methods and provide a starting point for choosing a method or combination of methods for a wide range of applications.
Keywords: NMR techniques